The Influence of Murabahah Financing and the Length of Financing Repayment on the Income of PNM Mekaar Syariah Customers in Bengkulu City - Daulay, Tri Hennarti; Idwal B; Afrianty, Nonie (Jurnal Internasional Ekonomi Islam, 2025)
Introduction: Micro, small, and medium enterprises play a vital role in economic growth, but this is not supported by sufficient capital for business actors. Objective: This study aims to determine the effect of murabahah financing and the length of repayment of financing on the income of PNM Mekaar Syariah customers in Bengkulu City. Method: The researcher used a quantitative method with primary data collection techniques, including questionnaires distributed to 50 respondents. The data analysis method used was multiple linear regression analysis with the SPSS 27.0 program. Results: Results Based on the calculated t value for the financing variable (X1), 2.660> t table value 2.01174, and its significance is less than 0.05 (0.00 <0.05). Moreover, the results of the calculated t value for the variable Length of Financing Repayment (X2) 2.263> t table value 2.01174, and its significance is less than 0.05 (0.005 <0.05). From the results of the simultaneous test (F TEST), the calculated F value is 10.947 while the F table is known df1 = 2 and df2 = 47 with a confidence level of 95%, then the F table is 3.20. Therefore, the calculated F 10.947> F table 3.20, and the significance value is 0.001 (<0.05). This means there is a simultaneous influence between the amount of financing and the length of the financing repayment period on the income level of PNM Mekaar Syariah customers in Bengkulu City, Selebar District. Implications: This shows that improving the quality of halal certification services in Banda Aceh City can also increase business actors’ satisfaction